Human papillomavirus genotypes associated with cervical precancerous lesions and cancer in the highest area of cervical cancer mortality, Longnan, China. Issue 1 (December 2017) - Zhao, Jin; Guo, Zhong; Wang, Qiang; Si, Tianbin; Pei, Shuyan; Wang, Chenjing; Qu, Hongmei; Zhong, Jianbin; Ma, Ying; Nie, Cong; Zhang, Dan
Abstract Background The mortality of cervical cancer in Longnan is as high as 39/10 million, ranking first in China. Methods Between 2012 to 2016, 329 samples with cervicitis, cervical intraepithelial neoplasia grade 1 to 3 (CINI to III), and invasive squamous cell carcinoma (SCC) were collected. HPV genotypes were examined with a validated kit for 23 different HPV subtypes. Results Compared to cervicitis, the HPV positivity is significantly higher in CINI, CIN II/III, and SCC (38.60%, 74.60%, 87.50% and 89.05%, P <  0.001) and the positivity is also higher in SCC compared to CINI (P <  0.01). The most frequently detected genotypes were HPV16 in cervicitis, HPV16, 58 and 52 in CINI and CIN II/III, and HPV16, 58 and 18 in SCC groups. HPV16 positivity in cervicitis, CINI, CIN II/III, and SCC patients were 45.46%, 46.81%, 60.32% and 78.69%, respectively. Compared to cervicitis and CINI, the odds ratios (OR) for SCC in HPV16 positive patients were 2.96 (95% confidence interval [CI]: 1.09–8.00, P <  0.05) and 4.20 (95% confidence interval [CI]: 2.05–8.61, P <  0.001), respectively. In addition, the multiple infections in cervicitis, CINI, CINII/III and SCC group are 9.09%, 27.66%, 26.98% and 25.41% and HPV16 + 58 was the most common combinations. Conclusion These findings highlight the key role of HPV16, 58, 52 and 18 in the development of CIN and SCC in Longnan women and a fully aware of regional differences in HPV genotype distribution are tasks for cervical cancer control and prevention.